Referentially used descriptions can be conditionalized - Csipak, EVa (Proceedings of the Amsterdam Colloquium, 2025)
In this paper I discuss referentially used DPs such as Alex’s spouse. I argue that they typically contribute not-at-issue content in the sense of Potts 2005 and Simons et al. 2010, in particular when they occur with adnominal if-clauses, such as Alex’s spouse, if they ever got married or some soccer player, if that’s what he is. I propose a multi-dimensional analysis, proposing that on the truth-conditional dimension, they simply refer to an individual, while on the non-truth-conditional dimension, they have a modal meaning.